2018
DOI: 10.1002/sdtp.12129
|View full text |Cite
|
Sign up to set email alerts
|

80‐2: AMQLED Display with Solution‐Processed Oxide TFT Backplane

Abstract: We report a 4-inch active matrix quantum-dot light-emitting diode (AMQLED) with solution-processed oxide thin-film transistors (TFTs) backplane and quantum-dot light-emitting diode (QLED). The oxide TFT exhibits the average field-effect mobility over 5 cm 2 V -1 s -1 . Highly efficient green QLEDs are demonstrated by using metal doped Li doped ZnO as an electron transporting layer, which exhibit the current efficiency over 63 cd A -1 .Author Keywords solution-processed oxide, TFT backplane, high efficiency QLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Thus, presently, n-type oxide TFTs, for example, indium gallium zinc oxide (IGZO), exhibiting high electron mobility ( µ e ) of >10 cm 2 V −1 s −1 and decent operational stability, are adopted for large-area and foldable AM-OLED displays. Various n-type oxide TFTs have also been utilized for AM-QLEDs [ 20 , 21 , 24 , 32 ], as shown in Figure 1 . Nevertheless, p-type TFTs are also needed to comply with various QLED architectures (e.g., normal and inverted structures) and solution-based QLED fabrication processes.…”
Section: Non-si Tft Backplane Technologymentioning
confidence: 99%
“…Thus, presently, n-type oxide TFTs, for example, indium gallium zinc oxide (IGZO), exhibiting high electron mobility ( µ e ) of >10 cm 2 V −1 s −1 and decent operational stability, are adopted for large-area and foldable AM-OLED displays. Various n-type oxide TFTs have also been utilized for AM-QLEDs [ 20 , 21 , 24 , 32 ], as shown in Figure 1 . Nevertheless, p-type TFTs are also needed to comply with various QLED architectures (e.g., normal and inverted structures) and solution-based QLED fabrication processes.…”
Section: Non-si Tft Backplane Technologymentioning
confidence: 99%
“…The implementation of active-matrix QLEDs (AMQLEDs) is highly meaningful for the realization of QLED displays. A few companies and research groups have demonstrated monochromic or full-color AMQLEDs [67][68][69][70][71][72][73], as shown in Figure 2. For the monochromatic AMQLEDs, the QD layer can be formed through spin-coating.…”
Section: Demonstration Of Active-matrix Qled Displaysmentioning
confidence: 99%
“…Both passive-matrix (PM) and active-matrix (AM) driving electrode systems may be used to realize display applications, where the latter is beneficial for a larger display area or higher resolution. In terms of AM-based QLED, the conventional device design is bottom-emitting, where the light emission is extracted from the glass substrate side [ 29 , 30 , 31 , 32 ]. However, the opening of the bottom-emitting device and the light intensity are limited by the opaque thin-film transistor (TFT) circuit in the AM backplane.…”
Section: Introductionmentioning
confidence: 99%